The Effect Of Peer Peer Education On The Level Of Knowledge and Attitudes About Examination of Breast Self Examination in Adolescent - Indri Bakti Salsabila, Dinar; Sri Hardjanti, Triana; Runjati (Napande: Jurnal Bidan, 2025)
Background: Early detection through Breast Self-Examination (BSE) is an easy and affordable preventive effort. Since peers strongly influence adolescents’ health behaviors, peer education is considered an effective way to increase their knowledge and attitudes toward BSE. Method: This study employs a quasi-experimental design with a pretest-posttest control group. The study included 42 female adolescents, divided into 21 participants each in the intervention and control groups. The intervention group was given peer education, and the control group was only given a leaflet, then the group's knowledge and attitudes were measured before and after the intervention, and data were collected using a questionnaire. Sampling used simple random sampling based on inclusion criteria, namely 10th grade students, students who were present during the study, and willing to be respondents. Result: There were differences in the intervention group after being compared with the control group. The results showed that the average increase in knowledge in the intervention group was 5.05, while in the control group it was 3.52, with a p-value of 0.004 (<0.05). The average increase in attitude scores in the intervention group was 6.71 compared to 2.86 in the control group, with a p-value of 0.001 (<0.05). Conclusion: The health education intervention was effective in improving respondents' knowledge and attitudes compared to the non-intervention group. Therefore, it is recommended that similar health education programs be implemented more widely in the community and that further research be conducted to assess their long-term effectiveness.